Supply channel coordination in a newsvendor model with two allocation quotas (2011)
The motivation for this work comes from an article written in 2007 by Jianli Li and Liwen Liu, who extend the classic problem of the newspaper seller by forming a simple supply chain in which the retailer makes an order to the manufacturer, and if it does not satisfy the demand, has the possibility of placing a second order within a limited quota and conditioned by the manufacturer. They analyze how to establish a coordination mechanism between the two parties so that the expected profit of the system is maximum. This work expands the described model, allowing the retailer to resort to a second reserve quota at the end of the period, under similar conditions, seeking to optimize the expected profit of the system. The possibility of channel coordination and the mechanism to achieve it are studied.